Competition and market structure of banking sector: a panel study of Jordan and GCC countries - Anwar Salameh Gasaymeh; Zulkefly Abdul Karim; Mariani Abdul Majid; Mansor Jusoh (Penerbit Universiti Kebangsaan Malaysia, 2014)
This paper examines the market structure and competitiveness of the banking industry in Jordan and the GCC countries during the period 2003-2010, using a method proposed by Panzar and Rosse (1987). Using a static and dynamic panel data framework for a sample of 90 commercial banks, the empirical results revealed that banks in Jordan and the GCC countries have generated their revenue under monopolistic competition. This finding indicates that banks in Jordan are able to compete with the banking sector in the GCC countries. Therefore, the Jordanian government should seriously consider joining the GCC group of countries in the future.